Roth 2012 Submarine Landforms in a Surge-Type Tidewater Glacier Regime, Engelskbukta, Svalbard (Arctic Data Center, 2013)
Abstract: Though surge-type glaciers make up a small percentage of the world’s outlet glaciers, they have the potential to further destabilize the larger ice caps and ice sheets that feed them during a surge. Currently, mechanics that control the duration and ice flux from a surge remain poorly understood. Here, we examine submarine glacial landforms in bathymetric data from Engelskbukta, a bay sculpted by the advance and retreat of Comfortlessbreen, a surge-type glacier in Svalbard, a high Arctic archipelago where surge-type glaciers are especially prevalent. These landforms and their spatial and temporal relationships, and mass balance from the end of the last glacial maximum, known as the Late Weichselian in Northern Europe, to the present. Beyond the landforms representing modern proglacial sedimentation and active iceberg scouring, distinct assemblages of transverse and parallel crosscutting moraines denote past glacier termini and flow direction. By comparing their positions with dated deposits on land, these assemblages help establish the chronology of Comfortlessbreen’s surging and retreat. Additional deformations on the seafloor showcase subterranean Engelskbukta as the site of active thermogenic gas seeps. We discuss the limitations of local sedimentation and data resolution on the use of bathymetric datasets to interpret the past behavior of surging tidewater glaciers.